Relationship between spiritual intelligence and social intelligence with job stress among teachers of Marivan County, Iran: Spiritual intelligence and social intelligence - Vahabi, Arezoo; Vahabi, Ahmad; Fakhri, Marzeyeh; Moradi, Masoud; Sayyad, Sirvan; Sayyadi, Mahnaz (Chronic Diseases Journal, 2023)
BACKGROUND: A teacher's job stress is a teacher's experience of negative and unpleasant feelings such as discomfort, anxiety, depression, and anger that are caused by some aspects of a teacher's work, and has unpleasant consequences. This study aimed to determine the relationship between spiritual intelligence and social intelligence with job stress in teachers of Marivan County, Iran, in 2016. METHODS: This was a cross-sectional descriptive-analytical study. The population of this study was education teachers of Marivan County; using a sample size formula, 443 of them were randomly selected. Data collection tools were Osipow Job Stress Scale, Spiritual Intelligence Scale, and Social Intelligence Scale. The data were collected in autumn and winter and were analyzed using SPSS software. RESULTS: 70.2% of the samples were men and the others were women. The mean of the teachers' job stress score was 165.43 ± 25.67 (total score of the questionnaire: 300). This score indicates that the occupational stress level of the samples is higher than the average. The mean score of spiritual intelligence of the teachers was 100.70 ± 11.63 out of 116, the total score of the questionnaire. Of the social intelligence total score (36), the mean score of social intelligence was 21.29 ± 4.72, which was higher than the average. CONCLUSION: The results of the study indicated that the occupational stress of teachers was higher than average, and this stress could have different reasons. Educational leaders and planners should look for reasons and factors that affect teachers' job stress.